The Impact of the Dictionary on Language Skills Among Arabic and Kurdish Language Students - A Comparative Field Study - Mama, Dr. Sanker Ali Mama; Al-Samad, Dr. Ziad Abdullah Abd Al-Samad Abd (Sulaimani Journal for Humanities, 2026)
The dictionary is an essential tool in developing linguistic skills among individuals, expanding the user's vocabulary, improving reading skills, enhancing deep understanding of texts, developing critical thinking, enhancing the user's writing skills, making writing more powerful and professional, as well as strengthening speaking skills, and contributing to developing the abilities of students, researchers, and users in various aspects of the language, including expanding vocabulary, increasing the user's vocabulary stock, and improving the four skills such as reading skills. The dictionary also enhances writing skills, as it helps the writer choose the appropriate words for the context of the text. Therefore, this research entitled (The Effect of the Dictionary on the Linguistic Skills of Arabic and Kurdish Language Students - A Comparative Field Study) consists of an introduction, two chapters, a conclusion, and a list of sources and references. The first section deals with (the dictionary and linguistic skills), and the second section: It is an applied study on the effect of the dictionary on the linguistic skills of students in the Arabic and Kurdish language departments at the University of (Salah al-Din) for the academic year (2024-2025), and at the end of the research, the research reached the most important conclusions addressed by this research.
Keywords: dictionary; language skills; contrastive study